Modern international law: challenges of war and prospects of Ukraine’s European integration - Bova , Yevhen; Materynko , Maryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2026)
The article examines the impact of contemporary international law on Ukraine’s European integration process under conditions of armed aggression. Particular attention is paid to the interaction between the implementation of the EU acquis communautaire and the application of international humanitarian law and international criminal law during wartime. The study substantiates that compliance with international legal obligations in the fields of human rights protection, accountability for war crimes, and the rule of law constitutes not only a source of international legitimacy for Ukraine, but also a fundamental prerequisite for sustainable progress toward EU membership. The article analyzes the legal framework of Ukraine’s European integration course, including the Association Agreement with the European Union, constitutional provisions, and sectoral legislation in the areas of justice and anti-corruption policy. The experience of selected EU Member States in implementing international legal standards during the accession process is summarized, and key lessons relevant to Ukraine are identified, taking into account the specific challenges caused by the ongoing armed conflict. The research highlights both positive and risk-related factors influencing Ukraine’s EU accession prospects in the context of the application of international law. Based on the conducted analysis, the article proposes a three-track model for reconciling European integration reforms with national security imperatives. The article concludes that an adaptive and prioritized implementation of the EU acquis, combined with effective international cooperation and controlled emergency measures, can preserve the trust of international partners and provide a stable foundation for Ukraine’s gradual and credible integration into the European Union, even under conditions of ongoing armed conflict.